The CB1 receptor is required for the establishment of the hyperlocomotor phenotype in developmentally-induced hypothyroidism in mice. (April 2017) - Giné, Elena; Echeverry-Alzate, Victor; Lopez-Moreno, Jose Antonio; Rodriguez de Fonseca, Fernando; Perez-Castillo, Ana; Santos, Angel
Abstract: Alterations in motor functions are well-characterized features observed in humans and experimental animals with thyroid hormone dysfunctions during development. We have previously suggested the implication of the endocannabinoid system in the hyperlocomotor phenotype observed in developmentally induced hypothyroidism in rats. In this work we have further analyzed the implication of endocannabinoids in the effect of hypothyroidism on locomotor activity. To this end, we evaluated the locomotor activity in adult mice lacking the cannabinoid receptor type 1 (CB1R −/− ) and in their wild type littermates (CB1R +/+ ), whose hypothyroidism was induced in day 12 of gestation and maintained during the experimental period. Our results show that hypothyroidism induced a hyperlocomotor phenotype only in CB1R +/+, but not in CB1R −/− mice. In contrast with our previous results in rats, the expression of CB1R in striatum and the motor response to the cannabinoid agonist HU210 was unaltered in hypothyroid CB1R +/+ mice suggesting that the cannabinoid system is not altered by hypothyroidism. Also, no effect of HU210 was observed in locomotion of CB1R −/− mice. Finally, since the dopaminergic system plays a major role in the control of locomotor activity we studied its function in hypothyroid wild type and knockout animals. Our results show no alteration in the behavioral response induced by the dopamine D1 receptor agonist SKF38393. However we observed a decreased response to the dopamine D2 receptor antagonist haloperidol only in hypothyroid CB1R +/+ mice, which might indicate potential alterations in D2R signaling in these animals. In conclusion, our data suggest that the cannabinoid system is necessary for the induction of hyperlocomotor phenotype in mice with developmentally induced hypothyroidism. Highlights: Hypothyroidism increased locomotor activity in CB1 +/+ mice but not in CB1 −/− mice. Hypothyroidism modifies the response to haloperidol in the brain of CB1R +/+ mice. CB1R knockout mice do not present an altered response to haloperidol. The absence of CB1R impairs the development of the hyperactive behavior in hypothyroid mice. CB1R gene expression is necessary for the hyperlocomotor phenotype induced by hypothyroidism.